Bacteriological Analysis and Antibiotic Sensitivity Pattern of Blood Culture Isolates in Kanti Children Hospital - Karki, Shubana; Rai, Ganesh Kumar; Manandhar, Rekha (Journal of Nepal Paediatric Society, 2010)
Introduction: As antibiotic sensitivity pattern to common pathogen has been changing day by day, so it has been necessary to study about bacteriological analysis and antibiotic sensitivity pattern. Therefore, the purpose of this study was to analyze on data on bacteremia in children, the pathogen involved and sensitivity pattern. Objectives: The aim of this study was to determine the bacteriological profile and antibiotic sensitivity pattern of blood culture isolates from Kanti Children Hospital. Method: All blood culture reports (n=9856) during one year period (April 2007 to March 2008) included in the study were analyzed and the sensitivity pattern were recorded. In this retrospective study, we reviewed records of patients from Kanti Children Hospital from April 2007 to March 2008. Results: The positivity of blood culture was 4.2% (414/9856). Out of them, 269 (65%) were positive for Staphylococcus aures, 121(29.3%) E coli, 13(3.1%) Klebsiella pneumonia, 6(1.4%) Streptococcus pneumonia and 5(1.2%) Streptococcus viridence. Staphylococcus aureus was found most sensitive to Chloramphenicol (88.8%) followed by Amikacin (87.5%), Ofloxacin (76.5%), Ciprofloxacin (72%) and least sensitive to Ampicillin, Cloxacillin and Penicillin. E.coli was found most sensitive to Amikacin (74.7%) followed by Ofloxacin (69.9%), Ciprofloxacin (56.4%) and least sensitive to Cephalexin, Gentamycin and Ampicillin. Klebsiella pneumoniae was found most sensitive to Amikacin (91.7%) followed by Ofloxacin (87.5%), Chloramphenical (81.8%) and least sensitive to Cotrimoxazole and Gentamycin. It is 100% resistance to Ampicillin and Erythromycin. Streptococcus pneumoniae was most sensitive to Penicillin, Chloramphenical (100%) followed by Ampicillin and Erythromycin (83.3%) and least sensitive to Cotrimoxazole. Streptococcus viridence was most sensitive to Chloramphenical (100%) followed by Erythromycin (80%), Penicillin (75%) and least sensitive to Cotrimoxazole. Conclusion: This highlights the variable nature of antibiotic susceptibility patterns both in time and location around different geographical locations and within the same country as well. Therefore, it is advisable to continuously evaluate the sensitivity-resistance pattern of isolates so as to make a rational use of antibiotics. Key words: Antibiotic sensitivity; bacteremia; blood culture; neonatal sepsis. DOI: 10.3126/jnps.v30i2.2482 J. Nepal Paediatr. Soc. May-August, 2010 Vol 30(2) 94-97